Photoautotrophic and Photomixotrophic Micropropagation of Three Potato Cultivars - Rahman, MH; Alsadon, AA (Journal of Bio-Science, 2009)
The present study was aimed to compare the photoautotrophic (PAM) and photomixotrophic micropropagation (PMM) of three potato cultivars (Hermes, Rosetta and Asterix). Cultures were initiated from single node explants and established in MS basal medium with some modifications. Potato plantlets responded in sugar-free media although sugar-containing media (PMM1 and PMM2) performed better as compared to that of sugar-free (PAM1 and PAM2) media. The PMM1 produced shoot length averaging 6.25 cm with 8.08 nodes and weighing 0.24 g fresh weight of plantlet. On the other hand, PAM1 grown culture produced 4.03 cm shoot length, 8 nodes and 0.06 g of fresh weight. Shoot length and fresh weight of plantlets were significantly higher in PMM1 and PMM2 based media. Whereas the number of nodes per shoot was not significantly different on media with or without sugar (except the media PAM2). Sugar and vitamin-free media ( PAM2 ) performed inferior in all the traits. Key words: Potato, Photoautotrophic and Photomixotrophic Micropropagation. Â doi: 10.3329/jbs.v15i0.2210 Â J. bio-sci. 15: 111-116, 2007